Regioselective Enzyme-Mediated Acylation of Polyhydroxy Natural Compounds. A Remarkable, Highly Efficient Preparation of 6'-Acetyl and 6'-O-Carboxyacetyl Ginsenoside Rg1 - B. Danieli; E. Ragg; L. Scaglioni; M. Luisetti; S. Riva; A. Bertinotti; E. Bombardelli (The Journal of Organic Chemistry, 1995)
Lipase B from Candida anturctica has been shown to be an efficient catalyst for the regioselective acylation of the dammarane type glucoside ginsenoside Rg1 (1) on reaction with vinyl acetate in t-AmOH, affording the corresponding 6’-O-acetyl derivative lb in high yield. The structure of lb was determined through a careful inspection of its lH NMR at 600 MHz, which allowed for the complete assignment of the signals of the sugar’s protons. The introduction of a carboxyacetyl residue was then investigated using different protocols. The best results were obtained with a two-step sequence involving the preliminary enzymatic acylation of 1 with bis(2,2,2-trichloroethyl) malonate to give the mixed malonyl derivative lf, followed by selective chemical hydrolysis with ZdAcOH to the 6’-O-carboxyacetyl ginsenoside Rg1 (le).